Fatty acid composition in cultured Amphiascoides neglectus (Copepoda: Harpacticoida) - Kassim, Zaleha; Hamzah, Amir Safwan; Hashim, Hidayah Atirah; Hasnan, Hazwani Hanim (ISAAC Scientific Publishing, 2019)
This study investigates the effect of salinity on the fatty acid profile of a harpacticoid copepod Amphiascoides neglectus exposed to constant laboratory lighting and temperature (25-26oC) at pH7 for 40 days. The results were compared with those cultured in the common open hatchery environment which is almost the same as in the natural ecosystem. Different fatty acid levels were determined using Gas Chromatography and Mass Spectrometry (GC-MS). Results showed that there were no significant differences (p>0.05) in fatty acid content for both 20ppt and 30ppt treatment but the percentage of EPA was higher in 20ppt. Harpacticoid copepods in the hatchery showed significantly (p<0.05) more fatty acids in 30ppt than 20ppt. EPA was also higher in harpacticoids cultured under 30ppt. Manipulation of salinity and temperature in combination of light factor for copepod rearing system could improve the deposition of fatty acids in their body.